Analisis Varians dan Uji Signifikansi F - Aghna, Hannah; Ramadhani, Mutia; Hidayah, Naillah; Panggabean, Hadi Saputra (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
This study discusses the use of Analysis of Variance (ANOVA) and the F-test for significance, which are statistical methods designed to test significant differences between the means of three or more groups. ANOVA works by comparing variability between groups, using the F-test to support the process based on the F-distribution to assess the significance of the observed differences. This article provides a comprehensive discussion of the fundamental concepts of analysis of variance, the steps involved in conducting the F-test, and the statistical interpretation of the test results. The explanation is presented in a systematic and easy-to-understand approach, making it helpful for researchers or students in understanding and applying ANOVA in the context of quantitative research. By understanding analysis of variance and the F-test for significance, researchers can draw valid conclusions based on data and improve the quality of evidence-based decision-making.